The Canadian dream: How social media is influencing Filipinos' migration decisions - Macalanda, Mariah Caress G. (Animo Repository, 2025)
This study examines the role of social media in the migration processes of Filipinos who have the desire or intention to move to Canada, focusing on how these tools assist in making sound choices. Using the Social Network Theory, this study analyzed how social media platforms and the interactions and connections formed in such, affect the migration decision-making and experiences of Filipinos. The study delved into how social media platforms' provision of pertinent information, the construction of social networks, and the shaping of lifestyle perceptions about the host countries contribute to Filipinos' migratory choices and experiences. Data and findings from a mixed-method approach of quantitative surveys and interviews conducted with Filipino migrants in Canada present a triangulation and enhance the understanding of how the use of social networks affect migration. Keywords: Migration Choices, Social Media, Influence